The Performance of Collective Business Group in Handling the Poor in Urban Areas - Anwar Sitepu (Balai Besar Litbang Pelayanan Kesejahteraan Sosial, 2017)
The number of poor people in Indonesia is still quite high, spreading in rural areas, urban areas, coastal areas, small islands and countries’ border. Government and community are keep trying to resolve this issue, however declining rate of the number of poor people tends to slow down, including in urban areas. This research aimed to know the performance of the collective business group (CBG) in handling the problems of the poor in urban areas. The research was conducted in two cities, namely Tomohon and Manado in North Sulawesi Province. The subject are the entire CBG that was formedin the fiscal year of 2013 in two cities, which were 10 CBG in Tomohon and 60 CBG in Manado. Data were collected by interview, observation and focus group discussion, in May and July 2016. In practice only as many as 9 in the city ofTomohon and 52 Kube in Manado found. The rsearch results show that the performance of the Kube relatively less well. The largest portion of the CBG have been disbanded 77.8 percent in Tomohon and 90.4 percent in Manado. CBG which are still active as much as two units in Tomohon and five units in Manado. More than half had already disbanded prior to the first anniversary. There are five main reasons that make CBG disbanded, namely business losses, members reluctant to continue their joint effort, natural disasters, and dissent. UEP suffered losses due to three factors, namely the high cost ofproduction, it is not economical, influenced by the weather. Meanwhile, CBGs that survive also less able to give significant additional income for its members. The overall performance of the CBG in two cities has not been sufficient to eradicate poverty. The low performance of the CBGs occur due to a series of program implementation process done professionally, tend to be oriented solely to administrative settlement. Project management has not taken control of technical activities with good substance, at all stages.